Using Legal Materials in Teaching Religion. - Sullivan, Winnifred Fallers (Teaching Theology & Religion, 2000)
Argues for the importance of using primary legal materials in teaching religion in the United States. List of legal materials useful for religious education; Advantages of using legal documents in religious studies classrooms; Account on an introductory course in American religion; Details on a seminar in religion and law.